2019
DOI: 10.1177/0003702819834575
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Spatial Light Modulators in Raman Spectroscopy

Abstract: Advances in consumer display screen technologies have historically been adapted by researchers across the fields of optics as they can be used as electronically controlled spatial light modulators (SLMs) for a variety of uses. The performance characteristics of such SLM devices based on liquid crystal (LC) and digital micromirror device (DMD) technologies, in particular, has developed to the point where they are compatible with increasingly sensitive instrumental applications, for example, Raman spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 86 publications
(144 reference statements)
0
13
0
Order By: Relevance
“…However, Raman imaging experiments require the acquisition of many thousands of spectra and, typically, total acquisition times for these, depending on the desired spectral quality, would be in the order of a few minutes to several hours. Recently, the application of spatial light modulators (SLM) in RS has been demonstrated to create multifoci or light scanning for excitation of Raman scattering [ 43 , 44 ] or for a combination of structured illumination with compressive detection to improve the acquisition speed of Raman imaging [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Raman imaging experiments require the acquisition of many thousands of spectra and, typically, total acquisition times for these, depending on the desired spectral quality, would be in the order of a few minutes to several hours. Recently, the application of spatial light modulators (SLM) in RS has been demonstrated to create multifoci or light scanning for excitation of Raman scattering [ 43 , 44 ] or for a combination of structured illumination with compressive detection to improve the acquisition speed of Raman imaging [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous works of the authors [4,24], it was shown that convex optimization methods can be applied to solve the problem (1) in the range of ±λ/2 of wavefront aberrations, which can be increased up to ±5λ without loss in accuracy. Gradient descent, Newton's method, or particle swarm are among of the lots of other methods [25], which could be implemented to solve the problem (1). Figure 1 illustrates the block diagram of wavefront aberrations measuring algorithm.…”
Section: Algorithm For Measuring Wavefront Aberrationsmentioning
confidence: 99%
“…New methods and devices with a wide variety of properties and parameters [1][2][3] are being developed based on controllable optical components due to the variety and flexibility of such devices. Microdisplays are used more and more often as metrological tools for monitoring parameters of laser beams, in adaptive atmospheric sounding systems, imaging optical holography systems, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] By enabling control over the cell-cell interaction, optical trapping has enabled investigation of the early events in intercellular biological processes, such as phagocytosis and synapse formation. [19,20] HOT-RMS has potential for studying interaction between parasites and host cells noninvasively, and observing the molecular specific changes of isotope labels from the very earliest stages. [18] Recently, an integrated HOT and RMS system was demonstrated to be powerful for measurement and manipulation of live cells and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Recently, an integrated HOT and RMS system was demonstrated to be powerful for measurement and manipulation of live cells and organisms. [19,20] HOT-RMS has potential for studying interaction between parasites and host cells noninvasively, and observing the molecular specific changes of isotope labels from the very earliest stages.…”
Section: Introductionmentioning
confidence: 99%